To the 90th Birthday of Petro Ivanovych Fomin (1930–2011) - Bakai, O. S.; Bar’yakhtar, V. G.; Gusynin, V. P.; Zagorodny, A. G.; Loktev, V. M.; Peletminskii, S. V.; Sitenko, Yu. O.; Slyusarenko, Yu. V.; Storizhko, V. Yu.; Shulga, M. F. (Ukrainian Journal of Physics, 2020)
-